2001
DOI: 10.1081/mst-100107842
|View full text |Cite
|
Sign up to set email alerts
|

Towards Autonomous Compilation of Turning Force Databases: Utilization of on-Machine Measurement of Machined Parts

Abstract: Several hitherto unrealized advantages would follow if each shop floor machine could compile its own machining database autonomously. This paper focuses on CNC turning to develop a shop floor friendly method for determining the cutting force component normal to the machined surface as well as the lumped static stiffness parameters of the machining set up solely from onmachine part inspection data gathered immediately after machining. It is shown that one can also estimate the shear and chip flow angles as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There are four variables and sixteen groups of experiments, so the equation of F 0.05 (4,11)=3.36 can be gotten by looking up the F-distribution tables. And the inequality of F>>3.36 can be satisfied perfectly in equations ( 3) - (5). Thus the regression equations are passed the significant test.…”
Section: The Experiments Results and Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…There are four variables and sixteen groups of experiments, so the equation of F 0.05 (4,11)=3.36 can be gotten by looking up the F-distribution tables. And the inequality of F>>3.36 can be satisfied perfectly in equations ( 3) - (5). Thus the regression equations are passed the significant test.…”
Section: The Experiments Results and Analysismentioning
confidence: 90%
“…Because the piezoelectric force sensor has the good performance of the better stiffness, sensitivity and dynamic performance etc. [5], and then the instruments for measuring the milling force mainly include the three-dimensional dynamic piezoelectric force sensor of Kistler 9265B and the electricity amplifier of Kistler5807 made in Switzerland and the computer data acquisition system. The maximum of milling force in the stable milling process serves as the measurements.…”
Section: Experiments Condition and Methodsmentioning
confidence: 99%
“…Because of the piezoelectric force sensor with better stiffness, sensitivity and dynamic performance etc. [8], and so the used measuring apparatus are mainly consisted of the three-dimensional dynamic piezoelectric force sensor of Kistler 9265B and the electricity amplifier of Kistler 5807 made in Switzerland and the computer data acquisition system.…”
Section: Test Conditions and Methodsmentioning
confidence: 99%
“…Kaldos points out that in high-speed cutting range, with the cutting speed increases to reduce cutting force in literature [3]. Cutting experiments showed that cutting force is not under all conditions in each cutting with the cutting speed increased with decreasing in literature [4]. Dumitrescu et al [5] found that when HSM hardened AISI H13 steel, cutting forces were higher when using worn tools as compared to the new ones.…”
Section: Introductionmentioning
confidence: 99%